An environment-friendly water-based treating agent for improving the phosphatability of high-strength steel
Patent Information
- Application Number
- CN202210919224.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-01
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-08-01
AI Technical Summary
该类技术可通过镀层处理赋予高强钢材料表面全新稳定特性,但能耗过大,不环保且需要增加电镀工序不适用于常规高强钢制造产线
[0023]本发明提供的一种用于高强钢可磷化性能改善的环保水基处理剂,使高强钢板表面具备优良的可磷化性能。本发明所述水基处理剂可满足高强度卷钢的高速连续生产过程和加工件制造过程应用;同时不影响成型,连接等加工性能,也是一种环保水基处理剂。
Smart Images

Figure BDA0003775692020000041 
Figure BDA0003775692020000051 
Figure BDA0003775692020000071
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal material surface treatment technology, and in particular to an environmentally friendly water-based treatment agent for the surface of high-strength coiled steel. This treatment agent can give the surface of high-strength steel plates excellent phosphating properties and is mainly used for surface modification treatment of high-strength steel. Background Technology
[0002] Phosphating originated in the early 20th century and is now widely used in the pretreatment process of automotive and home appliance coatings. After a century of technological development, it has formed a very mature technical system in terms of phosphating solution formulation, film formation mechanism, and action mechanism. Phosphating mainly involves the contact between the phosphating solution and the steel plate surface. Through acid etching and the oxidation effect of the accelerator, the hydrogen ion content in the interface area rapidly decreases, causing phosphate ions to gradually dissociate and form phosphate deposits on the metal ions. A uniform, fine, and completely covering phosphate layer on the metal surface can effectively improve coating adhesion and under-film corrosion resistance. For conventional car bodies, ordinary cold-rolled and galvanized materials show excellent and stable matching effects with phosphating. Currently, the application of phosphating for automotive materials with novel surface properties is a prominent issue and a research hotspot in the industry.
[0003] In recent years, with the advancement of steel material technology, the application of ultra-high strength steel has become increasingly widespread. Especially in the automotive industry, given its significant role in safety, environmental protection, and lightweighting, ultra-high strength steel technology has entered a stage of rapid development and widespread application. However, ultra-high strength steel requires the addition of more alloying elements, which directly alters the surface properties of the material. Studies have shown that the compositions formed by elements such as Mn, Si, and Cr through selective oxidation, which accumulate on the steel plate surface, often result in problems such as coarse crystallization and poor coverage during the phosphating process, significantly reducing its phosphating performance and failing to meet the requirements of coating applications. In response, major domestic and international steel suppliers have conducted numerous technical research studies on optimizing the phosphating performance of high-strength steel surfaces. Most of these studies focus on the selective oxidation control of elements such as Mn, Si, and Cr on the steel plate surface (e.g., CN102834531, CN102482728, CN102534359, CN108368590). This type of patented technology needs to effectively balance the degree of internal oxidation and the state of extreme surface oxidation while ensuring the control of selective oxidation precipitates on the surface. It has a narrow process window, is difficult to implement, and cannot be compatible with materials of different composition systems, requiring targeted process design.
[0004] Patents concerning the phosphating modification technology for high-strength steel surfaces mainly include two aspects: surface electrolytic pickling to remove the oxide-rich layer and surface flash plating to cover the oxide-rich layer. Publication numbers CN104136644, CN103124799, CN104508155, and CN103305749 propose methods for removing the oxide-rich layer affecting the phosphating performance of high-strength steel surfaces through an electrolytic pickling process on cold-rolled sheets. This type of technology is highly operable and compatible with materials of different compositions, but it also suffers from high energy consumption and environmental pollution, requiring an additional pickling process and is not suitable for conventional high-strength steel manufacturing lines.
[0005] Publication number CN104471115 proposes a method of applying zinc plating with a coverage of over 60% on the surface of steel plates via flash plating to optimize surface phosphating performance and resistance to sticking. Simultaneously, published literature also reports techniques for manufacturing high-strength steel with good phosphating properties through flash nickel and flash iron plating. These technologies can impart new and stable surface properties to high-strength steel materials through coating treatment, but they consume excessive energy, are environmentally unfriendly, and require additional electroplating processes, making them unsuitable for conventional high-strength steel manufacturing lines.
[0006] Developing an environmentally friendly water-based treatment agent that can optimize and control the phosphating performance of high-strength steel surfaces is of great significance for the efficient application and promotion of high-strength steel technology in automobiles. Summary of the Invention
[0007] The purpose of this invention is to provide an environmentally friendly water-based treatment agent that can be applied to the surface of high-strength steel for phosphate modification and optimization.
[0008] This invention, through theoretical analysis, extensive laboratory scientific research, and practical verification, has ultimately determined the technical route for an environmentally friendly water-based treatment agent for nano-modification of high-strength phosphate surfaces. Combining the typical surface characteristics of high-strength steel, a water-based treatment agent is formed, comprising one or more components including fluorinated compounds, metal ion compounds, organic acid compounds, and surfactants. This treatment agent can meet the application requirements of high-speed continuous production processes of high-strength coiled steel and the manufacturing processes of processed parts. Specific treatment methods include dipping, spraying, and roller coating to form a wet film on the steel plate surface. Blowing or drying allows the treatment agent to quickly form a surface modification layer of several nanometers thickness on the steel plate surface. This modified layer can form epitaxial active crystal nuclei on the steel plate surface with the same orientation as the phosphate crystals, thereby significantly improving the phosphate performance of high-alloy element (such as Mn, Si, Cr, Mo, etc.) high-strength steel plates. Simultaneously, it does not affect processing properties such as forming and joining.
[0009] The technical solution of the present invention:
[0010] A water-based, environmentally friendly, phosphate-modified surface-modifying agent for high-strength steel products is prepared by dissolving or dispersing a composition in an aqueous medium. The specific composition of the surface-modifying agent is as follows:
[0011] E. A compound selected from those containing fluoride ions;
[0012] F. A metal ion compound selected from those containing Cu, Zn, Mn, Ni, and Fe;
[0013] G. A compound selected from organic acids;
[0014] H. A compound selected from surfactants;
[0015] This invention relates to a surface treatment agent that can be diluted with 0 to 20 parts water for application, or it can be applied directly without adding water.
[0016] The metal ions involved in this invention are not limited to a specific valence state.
[0017] The aqueous treatment agent of this invention comprises compounds selected from those containing fluoride ions, including ammonium fluorotitanate, ammonium fluorozirconate, potassium fluorotitanate, and potassium fluorozirconate. The molar concentration of fluoride (F) in the solution is 0.3-1.8 mol / L, preferably 0.6-1.1 mol / L. This additive serves two purposes: firstly, it homogenizes surface etching; secondly, it allows titanium or zirconium to be deposited onto the material surface in a dotted manner, forming active sites conducive to phosphating nucleation. When the F content is below 0.3 mol / L, the film-forming properties of the surface treatment agent deteriorate, affecting the modification effect; when the F content is above 1.8 mol / L, the stability of the surface treatment agent tends to decrease significantly.
[0018] The aqueous treatment agent of this invention comprises one or more metal ion compounds containing Cu, Zn, Mn, Ni, and Fe, including: sulfates, carbonates, and nitrates containing copper ions; sulfates, phosphates, formates, and acetates containing Zn ions; phosphates, carbonates, and nitrates containing Mn ions; nitrates and oxalates containing Fe ions; and sulfates, nitrates, and carbonates containing Ni ions. The molar concentration of the metal ion compound in the solution is 0.05-0.6 mol / L, preferably 0.1-0.25 mol / L. This additive is mainly used to further replenish isomorphous nucleation sites for phosphating crystals. When the content is below 0.05 mol / L, it cannot effectively replenish phosphating nucleation sites; if the content is above 0.6 mol / L, the modified film thickness will be too large, resulting in a uniform passivation effect, directly affecting the coatability of the treated surface.
[0019] The aqueous treatment agent of this invention comprises organic acid compounds selected from compounds with complexing and chelating functions, including citric acid, oxalic acid, tannic acid, lactic acid, tartaric acid, and salicylic acid. The molar concentration of the organic acid compound in the solution is 0.03-0.4 mol / L, preferably 0.05-0.2 mol / L. This compound has a certain cleaning effect on the steel plate surface, and the reactants formed adhere to the steel plate surface, promoting the rapid nucleation and growth of the phosphating film. When the content is below 0.03 mol / L, the surface cleaning effect decreases significantly; if the content is above 0.4 mol / L, it significantly affects the stability of the treatment agent system.
[0020] The surface treatment agent of this invention mainly comprises surfactants such as sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecyl sulfonate, octadecylamine, and triethanolamine. The molar concentration of the surfactant in the solution is 0.002-0.015 mol / L, preferably 0.003-0.01 mol / L. The main function of this additive is to enhance the film-forming properties of the treatment agent, while simultaneously reducing the surface tension after film formation, optimizing the rapid wetting effect between the steel plate surface and the phosphating agent during the pre-coating process, thereby improving phosphating performance. When its content is less than 0.002 mol / L, the optimization of the film-forming properties of the treatment agent is not significant; when the content is greater than 0.015 mol / L, the film-forming quality of the treatment agent is significantly affected, and the optimization effect of phosphating performance after film formation decreases.
[0021] The environmentally friendly water-based treatment agent for improving the phosphating performance of high-strength steel described in this invention can be applied to continuous manufacturing lines for pickled and cold-rolled high-strength steel. A wet film is formed on the steel plate surface through methods such as immersion, spraying, and roller coating. By blowing or drying, the treatment agent can rapidly form a nanoscale surface modification layer on the steel plate surface, achieving a significant optimization of the phosphating performance of high-strength steel.
[0022] Beneficial technical effects of the present invention:
[0023] This invention provides an environmentally friendly water-based treatment agent for improving the phosphating properties of high-strength steel, giving the surface of high-strength steel plates excellent phosphating properties. The water-based treatment agent of this invention can meet the application requirements of high-speed continuous production processes of high-strength coiled steel and the manufacturing processes of processed parts; at the same time, it does not affect processing performance such as forming and joining, and is also an environmentally friendly water-based treatment agent. Detailed Implementation
[0024] To better understand the present invention, specific descriptions are provided through examples and comparative examples. However, the scope of the present invention is not limited by these examples. The surface treatment agent composition used and the type of steel plate treated are described below:
[0025] (1) Test specimen:
[0026] The material used in the examples is typical 80 kg-class ultra-high strength steel, 1.2 mm thick, and its composition is shown in Table 1.
[0027] Table 1. Composition information of the cold-rolled steel sheet used in the embodiments.
[0028]
[0029] (2) Sample processing and cleaning methods:
[0030] The material was cut into 30*70mm samples. It was then sprayed with an alkaline degreasing agent (pH=11-12) to remove dirt and oil adhering to the surface. After that, it was washed with pure water to remove any remaining alkaline components. After drying with cold air, it was ready for use.
[0031] (3) Composition of water-based surface treatment agents
[0032] The composition ratio and treatment method of the environmentally friendly water-based surface treatment agent used in the examples are shown in Table 2.
[0033] Comparative Example 4 is the original surface material that has not undergone this surface treatment.
[0034] Table 2. Examples and Surface Treatment Agents Used
[0035]
[0036] The surface-treated samples obtained through the above examples and comparative examples were coated with 1000 mg / m² rust-preventive oil and left to stand for one week before undergoing a phosphating performance evaluation before coating. The laboratory simulation, referencing the pre-coating process flow of an automotive factory, mainly included degreasing, surface conditioning, and phosphating. The relevant treatment agent used was the commercially available product of Pacrose, and the specific process parameters are shown in Table 3.
[0037] Table 3 Phosphating process parameters
[0038] Handling method soak spray soak soak spray spray drying Processing temperature 40℃ room temperature room temperature 35℃ room temperature room temperature 90℃ Processing time 90s 20s 30s 120s 20s 20s
[0039] After the samples were treated in the above manner, the coverage and size of the phosphating crystals were observed under a scanning electron microscope, and the phosphating film weight was tested using a chemical dissolution method. The specific methods are as follows:
[0040] (1) Assessment of Phosphate Crystallization Coverage
[0041] The phosphating surface of the sample was observed at 1000x magnification using a scanning electron microscope (equipment: Zeiss SIGMA 500), and the evaluation was based on the proportion of phosphating film coverage.
[0042] ◎: Phosphating film coverage = 100%
[0043] ○: 80% ≤ Phosphating film coverage < 100%
[0044] Δ: 60% ≤ Phosphating film coverage < 80%
[0045] ×: Phosphating film coverage < 60%
[0046] (2) Phosphate crystal size test
[0047] The phosphating surface of the sample was observed at 2000x magnification using a scanning electron microscope (Zeiss SIGMA 500). The average value of five randomly selected phosphating crystal lengths was measured using a scale bar.
[0048] (3) Phosphate film retest
[0049] First, the 30*70mm phosphated sample was weighed (using a Mettler MS-TS analytical balance) and recorded as W0. Then, the sample was immersed in the phosphated film removal solution (solution: 50g / L anhydrous chromic acid, temperature: 75℃) for 15 minutes. After removal, it was rinsed with deionized water for 40 seconds, dried with cold air, and then weighed a second time and recorded as W1.
[0050] The weight W of the phosphating film was calculated.
[0051] W = (W0 - W1) / S 样板表面积
[0052] As shown in Table 4, Examples 1-6 exhibited good phosphating performance in all evaluation items, with Examples 1, 2, 3, 4, and 6 demonstrating particularly excellent overall performance. A comparison between Examples 1 and Comparative Example 4 shows that the phosphating performance of materials treated with the treatment agent was significantly improved. A comparison between Example 6 and Comparative Example 1 shows that insufficient content of the treatment agent components cannot effectively improve the phosphating performance of the treated sample surface. Examples 1, 2, and Comparative Example 2 show that appropriate amounts of F-containing compounds and metal salts can optimize the phosphating performance of the sample surface; however, excessive addition increases the film thickness, hindering rapid phosphating film growth and leading to a decrease in phosphating performance. Examples 4 and Comparative Example 3 show that excessive surfactant addition affects the film-forming effect of the treatment agent, significantly reducing the optimization effect of phosphating performance on the treated sample surface. Examples 3, 4, and 5 show that the treatment agent can adapt to typical coating methods such as spraying, dipping, and roller coating, exhibiting broader process adaptability.
[0053] Table 4 Performance of Examples
[0054]
[0055] Of course, those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention and are not intended to limit the present invention. Any modifications or variations of the above embodiments that are within the spirit and essence of the present invention will fall within the scope of the claims of the present invention.
Claims
1. A water-based treatment agent for improving the phosphating properties of high-strength steel, characterized in that, This water-based treatment agent is prepared by dissolving or dispersing a composition in an aqueous medium. The specific composition of the water-based treatment agent is as follows: A. A compound selected from those containing fluoride ions; wherein the compound containing fluoride ions is selected from one or more of ammonium fluorotitanate, ammonium fluorozirconate, potassium fluorotitanate, and potassium fluorozirconate; and the molar concentration of F element in the water-based treatment agent solution is 0.3-1.8 mol / L; B. A metal ion compound selected from those containing Cu, Zn, Mn, Ni, and Fe; the molar concentration of the metal ion compound in the water-based treatment agent solution is 0.05-0.6 mol / L; C. A compound selected from organic acids; The molar concentration of organic acid compounds in the water-based treatment agent solution is 0.03-0.4 mol / L; the organic acid compounds include: citric acid, oxalic acid, tannic acid, lactic acid, tartaric acid, and salicylic acid organic acid compounds with complexing and chelating functions; D. A compound selected from surfactants; the molar concentration of the surfactant compound in the water-based treatment agent solution is 0.002-0.015 mol / L; Use directly without adding water.
2. The water-based treatment agent for improving the phosphating properties of high-strength steel according to claim 1, characterized in that, The molar concentration of F element in the water-based treatment agent solution is 0.6-1.1 mol / L.
3. The water-based treatment agent for improving the phosphating properties of high-strength steel according to claim 1, characterized in that, The metal ion compounds containing Cu, Zn, Mn, Ni, and Fe include: sulfates, carbonates, and nitrates containing copper ions; sulfates, phosphates, formates, and acetates containing Zn ions; phosphates, carbonates, and nitrates containing Mn ions; nitrates and oxalates containing Fe ions; and sulfates, nitrates, and carbonates containing Ni ions.
4. The water-based treatment agent for improving the phosphating properties of high-strength steel according to claim 1, characterized in that, The molar concentration of metal ion compounds in the water-based treatment agent solution is 0.1-0.25 mol / L.
5. The water-based treatment agent for improving the phosphating properties of high-strength steel according to claim 1, characterized in that, The molar concentration of organic acid compounds in the water-based treatment agent solution is 0.05-0.2 mol / L.
6. The water-based treatment agent for improving the phosphating properties of high-strength steel according to claim 1, characterized in that, Compounds selected from surfactants in water-based treatment agents include: sodium dodecyl sulfate, sodium dodecyl sulfonate, calcium dodecyl sulfonate, octadecylamine, and triethanolamine.
7. The water-based treatment agent for improving the phosphating properties of high-strength steel according to claim 1, characterized in that, The molar concentration of the surfactant compound in the water-based treatment agent solution is 0.003-0.01 mol / L.
8. The application of a water-based treatment agent for improving the phosphating properties of high-strength steel according to any one of claims 1-7 in a continuous manufacturing line for pickled high-strength steel and cold-rolled high-strength steel.
Citation Information
Patent Citations
Aluminum alloy passivating method
CN113122833A
Procedure for the application of a PTFE-based self-lubricating coating on a bearing element, and the bearings thus obtained
US5011738A